2016
DOI: 10.1002/jssc.201600470
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of biomarkers of liver and kidney injury in serum and urine using ultra-fast liquid chromatography with tandem mass spectrometry coupled with a hydrophilic interaction chromatography column: Application to monitor injury induced by E

Abstract: Fast and sensitive monitoring of drug-induced liver and kidney injury in early stage is beneficial. An ultrafast liquid chromatography with tandem mass spectrometry assay was developed and validated to simultaneously determine ten endogenous biomarkers in serum and urine, including hippuric acid, phenylacetylglycine, 5-oxoproline, cholic acid, taurine, indoleacetic acid, 3-indoxyl sulfate, guanidinosuccinic acid, guanidinoacetic acid and uric acid. A CAPCELL CORE PC column (2.1 × 150 mm, 2.7 μm) was adopted fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…From the untargeted experiment, hippuric acid, a common carboxylic acid found in the urine of horses and other plant eating species was the most abundant molecule identified followed by creatinine, a breakdown product of creatine that is commonly secreted through urine and is used to monitor normal kidney function and can be used as a urine control metabolite for normalization [ 50 ]. Phenylacetylglycine was also very abundant and is a gut microbial co-metabolite with hippuric acid and well-studied using LC-MS/MS methods from urine as phospholipidosis markers [ 51 , 52 ]. p-Cresol glucuronide is another common urine metabolite derived from intestinal bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…From the untargeted experiment, hippuric acid, a common carboxylic acid found in the urine of horses and other plant eating species was the most abundant molecule identified followed by creatinine, a breakdown product of creatine that is commonly secreted through urine and is used to monitor normal kidney function and can be used as a urine control metabolite for normalization [ 50 ]. Phenylacetylglycine was also very abundant and is a gut microbial co-metabolite with hippuric acid and well-studied using LC-MS/MS methods from urine as phospholipidosis markers [ 51 , 52 ]. p-Cresol glucuronide is another common urine metabolite derived from intestinal bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Hippuric acid is a product of amino acid metabolism by gut microbiota and has been shown to be part of metabolite panels that change in kidney injury. Urinary levels of hippuric acid have also been shown to significantly increase in acute kidney injury (85).…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of GSA and other toxic guanidine-based compounds has been reported to cause kidney dysfunction (Levillain, Marescau, Possemiers, Banchaabouchi, & De Deyn, 2001). Guanidine-based compounds were detected in patients with chronic renal failure by high-performance liquid chromatography, and the results showed that GSA levels were significantly elevated in the body, suggesting that GSA may be used as a biomarker of kidney damage (Tanaka, Takahashi, Mizokuchi, Shimada, & Koide, 1999;Zhang, Gu, Jiang, Bi, & Chen, 2016). GSA is produced from the oxidation of argininosuccinic acid (an amino acid) by free radicals (Perez, Epstein, Rietberg, & Loutzenhiser, 1978;Schepers et al, 2010).…”
Section: Discussionmentioning
confidence: 99%